Taalvermoë en originariteit - Peeters, Leopold (University of the Free State, 2008)
Language is not to be found in dictionaries or theories, but in speech itself. My quest is to understand what happens in speech. Language is not merely a means of communication but the manner in which one becomes oneself in one’s own body. Language is a means to self-realisation and thus to originarity. This position is argued by tracing a path via the speech events, the subject, poetry as originary speech, the philosophy of language, the complexity of language as a phenomenon, dualism and its origin, the living body as a victory over dualism, and the voice — to human understanding.

Taal bestaan nie in woordeboeke of teorieë nie, slegs in die spraak. Daarom wil ek verstaan wat gebeur as ’n mens praat. Spraak is nie net kommunikasiemiddel nie, maar die manier waarop die mens sigself in eie liggaam word. Taal is ’n vermoë tot selfuitbou en sodoende tot originariteit. Hierdie stelling word geargumenteer in ’n nadenke wat ’n pad loop via die taalgebeure, die subjek, die digkuns as originêre spraak, taalfilosofie, kompleksiteit van die taalfenomeen, dualisme en sy oorsprong, die lewende liggaam as oorwinning van die dualisme, die stem na menslike kennis.
Keywords: Language; Language ability; Originarity; Speech